Systematic Review on Clinical Authority of Nurses Worldwide - Yanto, Arief; Kustriyani, Menik (University of Muhammadiyah Semarang, 2023)
Background: The clinical authority of nurses is a critical aspect of healthcare delivery that influences patient outcomes and the overall effectiveness of health systems. This systematic review aims to synthesize recent evidence regarding the implementation of clinical authority among nurses worldwide. Methods: A comprehensive literature search was conducted across multiple databases, focusing on peer-reviewed articles published between 2018 and 2022. Studies were selected based on their relevance, methodological quality, and focus on clinical authority in nursing practice. Results: The review identified key themes, including the impact of clinical authority on patient care, the role of education and training, and the challenges faced by nurses in exercising their authority. Evidence consistently showed that empowering nurses with clinical authority leads to improved patient outcomes and satisfaction. Conclusions: The effective implementation of clinical authority in nursing is essential for optimizing patient care. Healthcare systems should prioritize policies that support the empowerment of nurses in clinical decision-making.